FDG‐PET/MRI imaging for the management of alveolar echinococcosis: initial clinical experience at a reference centre in Austria. Issue 6 (27th March 2019) - Lötsch, Felix; Waneck, Fredrik; Groger, Mirjam; Auer, Herbert; Kaczirek, Klaus; Rausch, Ivo; Wadsak, Wolfgang; Hacker, Marcus; Lagler, Heimo; Ramharter, Michael; Karanikas, Georgios
Abstract: Background: [ 18 F]‐2‐fluoro‐2‐deoxy‐D‐glucose (18F‐FDG) positron emission tomography/computed tomography (FDG‐PET/CT) imaging provides important information about the size and metabolic activity of lesions caused by Echinococcus multilocularis and is therefore recommended for the initial assessment and follow‐up of human alveolar echinococcosis (AE). The introduction of positron emission tomography/magnetic resonance imaging (PET/MRI) into clinical practice in affluent health care systems provides an alternative dual imaging modality, which has not yet been evaluated for AE. Objective: Here, we describe the initial clinical experience with comparative PET/CT and PET/MR imaging in four human AE patients at an Austrian reference centre. Results: PET/MR imaging showed comparable diagnostic capacity for liver lesions attributable to E. multilocularis infection, with a discrepancy only in the assessment of calcifications in one patient. Effective doses of radiation were 30.4–31 mSV for PET/CT, which were reduced in PET/MRI to the exposure of 18 F‐FDG only (4.9–5.5 mSv). Conclusions: PET/MRI provides comparable diagnostic information for AE management. The reduction in radiation exposure compared to PET/CT may be of particular importance for children and young patients not amenable for curative surgery requiring repeated long‐term follow‐up with dual imaging modalities. Further studies are warranted to prospectively evaluate the potential of PET/MRI in the management of AE. Abstract : Données de base: L'imagerie par la tomographie par émission de positrons au [18F]‐2‐fluoro‐2‐désoxy‐D‐glucose (18F‐FDG)/tomodensitométrie (TEP/TDM) fournit des informations importantes sur la taille et l'activité métabolique des lésions causées par Echinococcus multilocularis et est donc recommandée pour l'évaluation initiale et le suivi de l'échinococcose alvéolaire (EA) humaine. L'introduction de la tomographie par émission de positons/imagerie par résonance magnétique (TEP/IRM) dans la pratique clinique des systèmes de soins de santé aisés offre une alternative de modalité d'imagerie double, qui n'a pas encore été évaluée pour l'EA. Objectif: Nous décrivons ici l'expérience clinique initiale comparant les imageries TEP/TDM et TEP/IRM chez quatre patients humains atteints d'EA dans un centre de référence autrichien. Résultats: L'imagerie TEP/IRM a montré une capacité de diagnostic comparable pour les lésions hépatiques imputables à une infection à E. multilocularis, avec une divergence uniquement lors de l'évaluation des calcifications chez un patient. Les doses efficaces de rayonnement étaient de 30, 4 à 31 mSV pour la TEP/TDM, qui ont été réduites dans la TEP/IRM à une exposition au 18 F‐FDG uniquement (4, 9 à 5, 5 mSv). Conclusions: La TEP/IRM fournit des informations de diagnostic comparables pour la prise en charge de l'EA. La réduction de l'exposition aux rayonnements comparée à la TEP/TDM pourrait avoir une importance particulière pour les enfants et les jeunes patients ne pouvant pas subir de chirurgie curative nécessitant un suivi répété à long terme avec des modalités de double imagerie. Des études supplémentaires sont nécessaires pour évaluer de manière prospective le potentiel de la TEP/IRM dans la prise en charge de l'EA.